Assessment of abortion risk of sows on Japanese commercial farms infected with porcine epidemic diarrhea virus. (27th April 2020) - Furutani, Aina; Sekiguchi, Satoshi; Sueyoshi, Masuo; Sasaki, Yosuke
ABSTRACT: The objectives of this study were to assess abortion risk (AR) and the number of piglets that died during suckling periods per litter (DP) in farms infected with porcine epidemic diarrhea (PED) in relation to herd immunization procedures. Data were obtained from 91 farms in Japan that had PED infection during 2013 to 2014. The 91 PED‐positive farms were asked the number of abortions that occurred and DP for 3 months (1 month before PED outbreak (previous month), 1 month after PED outbreak (the month of PED), and from 1 month after PED outbreak to 2 months after PED outbreak (following month)). AR in each month was calculated as the number of abortions divided by sow inventory. Both AR and DP in the month of PED were higher than those in the previous and following months ( p < .05). Farms that performed a herd immunization procedure had higher AR and DP in the month of PED than those that did not perform the procedure ( p < .05). In summary, PED occurrence increased AR and DP.